Whole Genome Sequencing of the Asian Arowana (Scleropages formosus) Provides Insights into the Evolution of Ray-Finned Fishes - Austin, Christopher M. (Genome Biol Evol, 2015)
The Asian arowana (Scleropages formosus) is of commercial importance, conservation concern, and is a representative of one of the oldest lineages of ray-finned fish, the Osteoglossomorpha. To add to genomic knowledge of this species and the evolution of teleosts, the genome of a Malaysian specimen of arowana was sequenced. A draft genome is presented consisting of 42,110 scaffolds with a total size of 708 Mb (2.85% gaps) representing 93.95% of core eukaryotic genes. Using a k-mer-based method, a genome size of 900 Mb was also estimated. We present an update on the phylogenomics of fishes based on a total of 27 species (23 fish species and 4 tetrapods) using 177 orthologous proteins (71,360 amino acid sites), which supports established relationships except that arowana is placed as the sister lineage to all teleost clades (Bayesian posterior probability 1.00, bootstrap replicate 93%), that evolved after the teleost genome duplication event rather than the eels (Elopomorpha). Evolutionary rates are highly heterogeneous across the tree with fishes represented by both slowly and rapidly evolving lineages. A total of 94 putative pigment genes were identified, providing the impetus for development of molecular markers associated with the spectacular colored phenotypes found within this species.